Sanitário solar: a transdisciplinaridade como ferramenta de projeto, design e desenvolvimento sustentável - Hellmeister, Luiz Antonio Vasques [UNESP]; Palhaci, Maria do Carmo Jampaulo Plácido [UNESP]; Hellmeister, Victor; Palhaci, Talitha Plácido (My University, 2011)
The appropriate use of computer aided technologies, allied to the concepts and design guidelines, grounded in biology, stimulated the development of a solar toilet, able to convert human waste into compost, rich in nutrients for use in gardens, farms and small farms. This transdisciplinary approach is presented as a necessary tool to be used in academia, integrating and developing activities previously disconnected. The solar toilet also called green bathroom, combines the most modern concepts and technologies of computer-aided design, design, selection of materials and microbiological control, reaching biologically correct and safe composting of waste, ensuring the viability of the project terms of cost, deployment, use and environmental safety, such as supporting sustainable development. It is also planned to install a pilot project in a small community with the aim of assessing its implementation and use as a complementary activity and university extension.
Keywords: Solar toilet; CAD; Design; Waste; Sustentability